Physiological Age- and Sex-Related Profiles for Local (Aortic) and Regional (Carotid-Femoral, Carotid-Radial) Pulse Wave Velocity and Center-to-Periphery Stiffness Gradient, with and without Blood Pressure Adjustments: Reference Intervals and Agreement between Methods in Healthy Subjects (3–84 Years) - Daniel Bia; Yanina Zócalo (Journal of Cardiovascular Development and Disease, 2021)
In addition to being a marker of cardiovascular (CV) aging, aortic stiffening has been shown to be independently associated with increased CV risk (directly and/or indirectly due to stiffness-gradient attenuation). Arterial stiffness determines the rate at which the pulse pressure wave propagates (i.e., pulse wave velocity, PWV). Thus, propagated PWV (i.e., the distance between pressure-wave recording sites divided by the pulse transit time) was proposed as an arterial stiffness index. Presently, aortic PWV is considered a gold-standard for non-invasive stiffness evaluation. The limitations ascribed to PWV have hampered its use in clinical practice. To overcome the limitations, different approaches and parameters have been proposed (e.g., local PWV obtained by wave separation and pulse wave analysis). In turn, it has been proposed to determine PWV considering blood pressure (BP) levels (β-PWV), so as to evaluate intrinsic arterial stiffness. It is unknown whether the different approaches used to assess PWV or β-PWV are equivalent and there are few data regarding age- and sex-related reference intervals (RIs) for regional and local PWV, β-PWV and PWV ratio. Aims: (1) to evaluate agreement between data from different stiffness indexes, (2) to determine the need for sex-specific RIs, and (3) to define RIs for PWV, β-PWV and PWV ratio in a cohort of healthy children, adolescents and adults. Methods: 3619 subjects (3–90 y) were included, 1289 were healthy and non-exposed to CV risk factors. Carotid-femoral (cfPWV) and carotid-radial (crPWV) PWV were measured (SphygmoCor System (SCOR)) and PWV ratio (cfPWV/crPWV) was quantified. Local aortic PWV was obtained directly from carotid waves (aoPWV-Carotid; SCOR) and indirectly (generalized transfer function use) from radial (aoPWV-Radial; SCOR) and brachial (aoPWV-Brachial; Mobil-O-Graph system (MOG)) recordings. β-PWV was assessed by means of cardio-ankle brachial (CAVI) and BP-corrected CAVI (CAVIo) indexes. Analyses were done before and after adjustment for BP. Data agreement was analyzed (correlation, Bland-Altman). Mean and standard deviation (age- and sex-related) equations were obtained for PWV parameters (regression methods based on fractional polynomials). Results: The methods and parameters used to assess aortic stiffness showed different association levels. Stiffness data were not equivalent but showed systematic and proportional errors. The need for sex-specific RIs depended on the parameter and/or age considered. RIs were defined for all the studied parameters. The study provides the largest data set related to agreement and RIs for stiffness parameters obtained in a single population.